Prospects for the «Green» economy of Kazakhstan (Eurasian Journal of Ecology, 2016)
Dulambayeva R.T., Boluspayev Sh. A., Al-Farabi Kazakh National University, Almaty. Article: Prospects for the «Green» economy of Kazakhstan. This article describes prospects of Kazakhstan’s transition to a green economy, which today is relevant to many countries. Proposal of the President of the Republic of Kazakhstan for the further development of the world economy are the most discussed. In Kazakhstan was organized annual Astana Economic Forum, based on which recommendations have been made, about the development of the global economy. In his speech, the President noted that Kazakhstan in spite of huge reserve of hydrocarbons, goes to the development of renewable energy sources. The article also gives thestatistics of renewable energy consumption in some countries of the world and Kazakhstan, the theoretical and the economic potential of energy production from renewable sources.
Keywords: «Green» economy; energy; renewable energy; innovation and development